Cutaneous sarcoidosis in a melanoma scar: A case report. (September 2019) - Fournier, Cynthia; Vallée, Sheila; Perron, Émilie; Thérien, Geneviève
Sarcoidosis is an inflammatory multisystemic disease of unknown etiology with multiple presentations of cutaneous lesions. It characteristically infiltrates scars due to several kind of trauma such as surgery, tattoo and even herpes zoster. We present a case of a 65-year-old woman with progressive distal paresthesia and motor weakness. She was referred to our dermatology clinic for a new violaceous nodular plaque within an old melanoma scar on the posterior neck. On positron emission tomography–computed tomography, there were multiple enlarged thoracic lymphadenopathy and a fluorodeoxyglucose-avid cutaneous lesion on the posterior neck, right in the melanoma scar. Cutaneous and nerve biopsies showed non-necrotising granulomas, supporting the diagnosis of systemic sarcoidosis and excluding melanoma recurrence with metastasis. It is the first case of cutaneous sarcoidosis arising within a melanoma scar. Interestingly, patients with melanoma have a higher risk of sarcoidosis.